Cahul District in the First Weeks of the Soviet Occupation (June-August 1940): Array - Cornea, Sergiu (Journal of Danubian Studies and Research, 2020)
As a result of direct diplomatic and military pressure exerted by the Soviet Union and blackmail by Germany and Italy in support of the aggressor, in June 1940 the Romanian administration and army left the territory of Bessarabia. The aim of the research is to reconstruct the events that occurred in a very complex and equally controversial period in the history of Cahul county –the establishment of the soviet occupation regime in summer 1940. In order to elucidate the subject, was used the method of content analysis of the official documents drawn up by the competent authorities of the “Lower Danube” Land, contained in the archive funds. A reliable source of information on the early days of soviet occupation is the refugees’ testimonies from Bessarabia. Although they provided stoning information, marked by personal feelings, they are still an important source of information because they were provided by eyewitnesses of the events. From the very first days of soviet occupation, soviet-type power structures were created in Bessarabia, and a number of political, economic, social and propaganda measures were taken to establish the soviet regime as soon as possible. The repressive measures taken by the new authorities caused discontent among the population, causing disappointment even to those who enjoyed the “moment of liberation”.